POLA PENETAPAN HARGA DALAM PEMBIAYAAN MURABAHAH DI BANK SYARI’AH (Analisis Managemen Keuangan Islam) - Mugiyati Mugiyati (Al Hikmah: Jurnal Studi Keislaman, 2013)
Financing is one of the bank's main tasks, namely providing facilities for the provision of funds to meet the needs of those who are deficit units. According to the nature of its use of financing, among others, can be divided into two, namely: for the purposes of production and consumption. In the conventional banks, the principle financing system in savings and loan. Banks lend money in return for interest. On Shariah banks as non-interest-based bank financing for the production and inventory financing needs do be done with principle of trading in two stages. First; banks hold (buy from suppliers in cash) the goods that is needed by customers. Second, the bank sold to customers with deferred payment and to take advantage, according to the collective agreement. In principle, the financing that’s done by conventional bank and shariah banks have differences. But the operational realities seem both have in common. On conventional bank loans given to customers, restored by the addition or Mark-Up. The returned number is higher than the real value received by the customer. On Shariah bank though trading principled, there is also an additional element (profit margin) on capital due to payment delays.